The systems for financing public pensions and their current tax treatment - Aguilar-Segado, Carlos David (My University, 2022)
The demographic analysis of the population, the social security budget, types of pensions as well as the revaluation of pensions is carried out. In addition, alternative and complementary systems, criteria for ensuring adequate pensions and other instruments for financing pensions.
Institute for Austrian and International Tax Law (WU Vienna University of Economics and Business)
Keywords: Pensiones-Impuestos; public; pensions; tax; treatment